Professional competence as a benchmark for a European space of vocational education and training - Grollmann, Philipp [Verfasser] (My University, 2008)
"The paper's aim is to present a critical review of the current European process of co-operation in VET with a special view to the European Qualification Framework and its competence orientation. The approach reviews the official documentation and the consultation process and a contrastive analysis of the state of the art of research and developments in VET. In order to make European VET a direct contribution to the revised Lisbon agenda, a more concise shared vision with regard to the processes and structures of vocational education might be needed. Research and development activities in the European Union should be integrated towards an agenda that covers structures, conditions and processes of learning for the world of work." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; Berufsbildung; Kompetenzorientierung; Europäischer Qualifikationsrahmen; Europäischer Bildungsraum; Europa